Industrial training final report: Putrajaya Marriot Hotel / Muhammad Afiq Helmy - Helmy, Muhammad Afiq (Universiti Teknologi MARA, Pulau Pinang, 2024)
The Putrajaya Marriott Hotel, nestled within IOI Resort City in Malaysia's administrative capital, is a premier 5-star destination offering luxurious accommodations and world-class amenities. Just 25 minutes from Kuala Lumpur and conveniently located near Kuala Lumpur International Airport, the hotel features 488 elegantly designed rooms and suites equipped with modem conveniences like air conditioning, high-speed internet, and in-room safes. Culinary options include the vibrant Zest Lifestyle Restaurant, Cantonese fusion at Summer Palace, and authentic Japanese cuisine at Midori. Guests can also enjoy leisure facilities like a sprawling outdoor pool, a children’s pool, a well-equipped health club, and a rejuvenating spa. Catering to both business and leisure travellers, the hotel boasts 13 versatile meeting rooms and an expansive event space of over 32,000 square feet, ideal for conferences, weddings, and grand celebrations. Adjacent to the Palm Garden Golf Club, the hotel offers seamless access to premier golfing experiences. As part of Marriott International, the Putrajaya Marriott Hotel ensures a perfect blend of modem sophistication and local charm, making it a standout choice for visitors seeking luxury and convenience in the heart of Malaysia.